Digital Transformation in HR and Employee Capability as Determinants of Financial Innovation: Evidence from Bank Central Asia - Wattilete, Litha Clara; Rakhmat, Rakhmat; Panggabean, Bungaran; Halik, Maria Yessica (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study examines the influence of digital transformation in human resources (HR) and employee capability on financial innovation at Bank Central Asia (BCA). Employing a quantitative approach, data were collected through a structured survey of 120 employees across key divisions. Multiple regression analysis revealed that employee capability has a significant positive effect on financial innovation, underscoring the importance of digital literacy, adaptability, and problem-solving skills in fostering new financial products and services. Conversely, digital transformation in HR was found to have no direct significant impact on financial innovation when assessed individually. However, together, both factors significantly influence financial innovation, highlighting the synergistic relationship between advanced digital HR systems and competent employees. These findings emphasize the necessity of integrating HR digitalization with robust capability-building initiatives to fully leverage technological investments. The study contributes to the literature by providing empirical evidence from Indonesia’s banking sector and offers practical insights for organizations aiming to strengthen innovation through a balanced focus on technology and human capital.